Programação linear inteira mista na roteirização de coleta seletiva - Souza, Giulia Milena Braga de (2024)
This study’s objective is to develop a mathematical model that makes possible to find the best routes for selective waste collection in the city of Biritiba Mirim. A literature review on existing concepts and models was realized. So, a methodology with an abstract and quantitative approach was used, in which the data source is natural and the resolution model is Mathematical Programming. The method chosen for the resolution is the Mixed Integer Linear Programming applied using the library called ORTools, which is a free tool, on Python, the model implemented is available in the present work. With this model, was found a solution that generated three distinct routes with a total distance of 140,390 meters, managing to serve all 24 neighborhoods of the city.